Delirium in the intensive care unit and its importance in the post-operative context: A review - Ní Chróinín, Danielle; Alexandrou, Evan; Frost, Steven A. (Frontiers in Medicine, 2023)
The burden of delirium in the intensive care setting is a global priority. Delirium affects up to 80% of intensive care patients; an episode of delirium is often distressing to patients and their families, and in patients within, or outside of, the intensive care unit (ICU) setting, is associated with poor outcomes. In the short term, such poor outcomes include longer stay in intensive care, longer hospital stay, increased risk of other hospital-acquired complications, and increased risk of hospital mortality. Longer-term sequelae include cognitive impairment, and functional dependency While medical category of admission may be a risk factor for poor outcomes in critical care populations, outcomes for surgical ICU admissions are also poor, with dependency at hospital discharge exceeding 30% and increased risk of in-hospital mortality, particularly in vulnerable groups, with high-risk procedures, and in resource-scare settings. A practical approach to delirium prevention and management in the ICU setting is likely to require a multi-faceted approach. Given the good evidence for the prevention of delirium among older postoperative outside of the intensive care setting, simple non-pharmacological interventions should be effective among older adults post-operatively cared for in intensive care setting. In response to this the future ICU environment will have a range of organisational and distinct environmental characteristics that are directly targeted at preventing delirium.